American bullfighter [videorecording (DVD)] - LeMay, Alex, 1966-; Reynolds, Michael (Cinema Libre Studio ; Cinema Libre Distribution, 2008)
Documentary that explores filmmaker Alex LeMay's recovery from alcoholism using bullfighting as his method of rehabilitation and redemption.